Bridging Clarity and Conscience: Systematic Approaches to Interpretability and Ethics in AI-Driven Data Science - Venkata Tadi (North American Journal of Engineering Research, 2021)
As artificial intelligence (AI) continues to integrate into data science, the imperative to ensure both interpretability and ethicalintegrity of AI-driven models becomes increasingly critical. This research explores systematic approaches to address these dual imperatives, offering a comprehensive framework that balances technical transparency with ethical considerations. By examining advanced methods for model interpretability, such as SHAP values and LIME, this study elucidates how complex AI models can be made more understandable to stakeholders across diverse industries. Concurrently, it delves into the ethicaldimensions of AI deployment, proposing robust ethical guidelines and frameworks that promote fairness, accountability, and transparency. Through detailed case studies in healthcare, finance, and other sectors, this research demonstrates practical applications of these approaches, highlighting both successes and ongoing challenges. The findings aim to provide actionable insights for practitioners and policymakers, ensuring that the deployment of AI in data science not only advances technologicalcapabilities but also adheres to stringent ethical standards. Ultimately, this study seeks to bridge the gap between clarity and conscience, fostering an AI-driven future that is both innovative and responsible